En-face optical coherence tomography in the diagnosis and management of age-related macular degeneration and polypoidal choroidal vasculopathy - Lau, Tiffany (Indian J Ophthalmol, 2015)
Optical coherence tomography (OCT) is a noninvasive imaging modality providing high-resolution images of the central retina that has completely transformed the field of ophthalmology. While traditional OCT has produced longitudinal cross-sectional images, advancements in data processing have led to the development of en-face OCT, which produces transverse images of retinal and choroidal layers at any specified depth. This offers additional benefit on top of longitudinal cross-sections because it provides an extensive overview of pathological structures in a single image. The aim of this review was to discuss the utility of en-face OCT in the diagnosis and management of age-related macular degeneration (AMD) and polypoidal choroidal vasculopathy (PCV). En-face imaging of the inner segment/outer segment junction of retinal photoreceptors has been shown to be a useful indicator of visual acuity and a predictor of the extent of progression of geographic atrophy. En-face OCT has also enabled high-resolution analysis and quantification of pathological structures such as reticular pseudodrusen (RPD) and choroidal neovascularization, which have the potential to become useful markers for disease monitoring. En-face Doppler OCT enables subtle changes in the choroidal vasculature to be detected in eyes with RPD and AMD, which has significantly advanced our understanding of their pathogenesis. En-face Doppler OCT has also been shown to be useful for detecting the polypoid lesions and branching vascular networks diagnostic of PCV. It may therefore serve as a noninvasive alternative to fluorescein and indocyanine green angiography for the diagnosis of PCV and other forms of the exudative macular disease.